Task Based Language Teaching for EFL Writing Development - Nihta V. F. Liando; Rinny Rorimpandey (English Education Department, 2025)
One aspect of English that is difficult for students to master is writing because it requires the right method technique in teaching after the pandemic For this reason this research was appointed with the aim at knowing whether the TBLT method has an impact on the students English learning process especially for their writing skill This research was conducted in class VIII of junior high school students because this is an experimental study a pre experimental design is used with the type of one group pre test and post test In addition in assessing the writing of students this study adapts the writing rubric of Brown 2007 The results showed that TBLT has a very significant effect on students writing this can be seen in the mean scores of the pre test and post test However considering also the situation of students at the time of the study it is hoped that further researchers or readers can examine more deeply about the learning losses found in this study or can use the results of the research as a starting point for learning problems during the new normal < p>